2019
DOI: 10.1088/1361-6498/ab29a3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of long-term risks of secondary cancer in paediatric patients with brain tumours after boron neutron capture therapy

Abstract: This study firstly explored the risks of secondary cancer in healthy organs of Chinese paediatric patients with brain tumours after boron neutron capture therapy (BNCT). Three neutron beam irradiation geometries (i.e. right lateral, top to bottom, posterior to anterior) were adopted in treating patients with brain tumours under the clinical environment of BNCT. The concerned organs in this study were those with high cancer morbidity in China (e.g. lung, liver and stomach). The equivalent doses for these organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(43 reference statements)
0
5
0
2
Order By: Relevance
“…When comparing neutron beam geometries, the authors concluded that the lifetime attributable risk of secondary malignancy was lower with posterior-to-anterior arrangement compared to right-lateral and top-to-bottom. Younger patients and female patients also had higher risks of secondary malignancy (89). In Japan, only 1 out of 180 patients treated for malignant brain tumors since 1968 developed multiple radiation-induced meningiomas in the treatment field (90).…”
Section: Pediatricsmentioning
confidence: 99%
“…When comparing neutron beam geometries, the authors concluded that the lifetime attributable risk of secondary malignancy was lower with posterior-to-anterior arrangement compared to right-lateral and top-to-bottom. Younger patients and female patients also had higher risks of secondary malignancy (89). In Japan, only 1 out of 180 patients treated for malignant brain tumors since 1968 developed multiple radiation-induced meningiomas in the treatment field (90).…”
Section: Pediatricsmentioning
confidence: 99%
“…In the same way, in patient contour images, voxels inside of patients are given a value of 1, and those outside of patients are given a value of 0. The 3D therapeutic dose for BNCT consists of four parts, that is, boron dose ( 10 B(n, α) 7 Li), fast neutron dose ( 1 H(n, n') 1 H), thermal neutron dose ( 14 N(n, p) 14 C), and gamma dose. Since fast neutron dose and thermal neutron dose are all caused by the protons and share the same relative biological effectiveness (RBE) factors, these two dose distributions are added and the result is named as proton dose in this study.…”
Section: Configuration Of 3d U-netmentioning
confidence: 99%
“…Given its high biological effectiveness, BNCT has unique advantages in the treatment of recurrent head and neck malignancies, glioblastoma, and melanomas, and the therapeutic effect has been demonstrated in some existing clinical cases. [7][8][9] An accurate BNCT treatment plan is the key to guiding the actual treatment. 10 Considering the complexity of neutron transport, current BNCT treatment planning systems (BNCT-TPSs) for example, NCT_Plan, 11 simulation environment for radiotherapy applications (SERA), 12 THORplan, 13 NeuCure system, 14 and JAEA computational dosimetry system, 15 all use the Monte Carlo (MC) method to evaluate the therapeutic dose.…”
Section: Introductionmentioning
confidence: 99%
“…44 Glioblastomların tedavisinde bor bileşiklerinin kullanılmasıyla birlikte Bor Nötron Yakalama Tedavisi [Boron Neutron Capture Therapy (BNCT)] ile bor bileşiklerinin sentezine odaklanan çalışmaların sayısı artmıştır. [45][46][47][48] Düşük molekül ağırlıklı bor içeren ilaçlar olan borfenilalanin ve sodyum borkaptat beyin tümörlerinin tedavisinde kullanılmaya başlamıştır. 46 BNCT metodu güncel olarak kanser tedavilerinde kullanılmaya başlanmıştır.…”
Section: Beyi̇n Tümörleri̇unclassified
“…Bu tedavinin en önemli artısı, ameliyatın riskli olduğu kanser hastaları için bir umut olmasıdır. [48][49][50][51]…”
Section: Beyi̇n Tümörleri̇unclassified